Anandpur, the city of bliss - Mohinder Singh 1941-; Shankar, Sondeep (New Delhi UBS Publishers' Distributors, 2002)
History of Anandapur S?ahib, town in Punjab, India and a major Sikh center.
Published in association with National Institute of Panjab Studies.
Keywords: Anandapur Sahib (India) -- Pictorial works; Anandapur Sahib (India) -- History